2020
DOI: 10.1246/cl.200031
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Polymerization and Functions of Isoxazole Ring Monomers

Abstract: He then joined the group of Prof. Julius Rebek Jr. at The Scripps Research Institute (19992000). In 2000, he was promoted to an Associate Professor of Chemistry at Hiroshima University. He has been a Full Professor since 2007. His research interests embrace the development of photoactive supramolecular polymer materials and graphene-based functional materials. Takehiro Hirao received a BSc degree in chemistry in 2011, an MSc degree in organic chemistry in 2013, and a Ph.D. degree in 2016 in organic chemistry f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 167 publications
1
10
0
Order By: Relevance
“…[85] Our group also reported stacked supramolecular systems. [86] These systems demonstrated that suitably organized 3D structures display unique architectures.…”
Section: Self-assembly By π/π Stacking Interactions (Route B)mentioning
confidence: 99%
“…[85] Our group also reported stacked supramolecular systems. [86] These systems demonstrated that suitably organized 3D structures display unique architectures.…”
Section: Self-assembly By π/π Stacking Interactions (Route B)mentioning
confidence: 99%
“…These domains can in principle be utilized for developing functional materials such as supramolecular aggregates. Suitably decorated small aromatic molecules can organize stacked supramolecular aggregates [4–12] . Examples are C 3 ‐symmetric benzene‐1,3,5‐tricarboxamide derivatives [12] and hexa‐ peri ‐benzocoronene derivatives [11] .…”
Section: Figurementioning
confidence: 99%
“…Suitably decorated small aromatic molecules can organize stacked supramolecular aggregates. [4][5][6][7][8][9][10][11][12] Examples are C 3 -symmetric benzene-1,3,5-tricarboxamide derivatives [12] and hexa-peri-benzocoronene derivatives. [11] These species self-assembled to form one-dimensional structures that assembled to organize unique morphologies, such as helical and tubular structures.…”
mentioning
confidence: 99%
“…Phenyl isoxazolyl benzene derivatives are flat conjugated molecules that form helical stacked supramolecular assemblies driven by dipole–dipole and π–π stacking interactions. The helical conformations are observed to be in equilibrium between plus (P) and minus (M) helices. Incorporating chiral moieties into the phenyl isoxazolyl benzenes turned off the racemic equilibrium, resulting in CPL-active one-handed helical assemblies. In 2016, our group demonstrated that carbazole-cored phenyl isoxazolyl benzene formed stacked supramolecular assemblies in a cooperative fashion .…”
Section: Introductionmentioning
confidence: 99%